2016
DOI: 10.1377/hlthaff.2016.0724
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Books: Public Libraries As Partners For Population Health

Abstract: Public libraries are not usually included in discussions about improving population health. They are, however, well positioned to be partners in building a culture of health through programming that addresses the social determinants of health. The Healthy Library Initiative, a partnership between the University of Pennsylvania and the Free Library of Philadelphia (the public library system that serves the city), has undertaken such efforts in Philadelphia. In this article we report findings from an assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 14 publications
5
89
0
Order By: Relevance
“…Higher literacy, including health literacy, is associated with increased levels of fulltime employment, on-time high school graduation rates, and a twofold reduced risk of uncontrolled diabetes (7–9). Recent research conducted in Philadelphia showed that public libraries often engage in health-related roles that extend beyond circulation of reading materials (1012). More than a third of inquiries to public librarians include questions about health (13).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher literacy, including health literacy, is associated with increased levels of fulltime employment, on-time high school graduation rates, and a twofold reduced risk of uncontrolled diabetes (7–9). Recent research conducted in Philadelphia showed that public libraries often engage in health-related roles that extend beyond circulation of reading materials (1012). More than a third of inquiries to public librarians include questions about health (13).…”
Section: Introductionmentioning
confidence: 99%
“…Public libraries also serve as places of refuge for vulnerable populations, including people experiencing mental illness, homelessness, immigration challenges, and trauma (12,14,15). Library staff members regularly assist patrons who have unmet health and social needs, but feel ill-equipped to address these patron needs (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In street intercept interviews with 77 residents [11], participants expressed how the city's diversity was both an asset and a challenge-and they saw a role for the library in fostering intergroup relationships and understanding. This finding was particularly compelling because of its relevance across the USA, where there are over 9000 public libraries, which host over 1.5 billion visits annually [7].…”
mentioning
confidence: 99%
“…In addition to offering access to books and electronic resources, the library actively addresses the social determinants of health, offering educational, social, and cultural programming that engages more than 500,000 diverse Philadelphians annually. And library staff members are committed to answering the call for strengthening the community and its health [11]. Public libraries are particularly well-suited to this task, offering a vital common ground, and a place for cross-cultural and intergenerational dialogue-and offering hope for greater integration and tolerance in our Bhighly sorted^city.…”
mentioning
confidence: 99%